EVALUASI KEBERHASILAN LEMBAGA PERKREDITAN DESA (LPD) DALAM MENGGERAKKAN SOSIAL EKONOMI MASYARAKAT PEDESAAN (Studi Pada Lembaga Perkreditan Desa (LPD) Desa Adat Pekutatan) - Pera Sundarianingsih (Jurnal Ekonomi Pembangunan, 2014)
This study aimed to evaluate the success of Village Credit Institutions in moving the social economy of rural communities. The indicator that shows the success Village Credit Institutions observed from three (3) aspects, namely Management, Financial Performance, and the role of socio-economic Village Credit Institutions in mobilizing rural communities. The results of this study can be concluded that Village Credit Institutions Management Pekutatan Village People is good enough. Financial performance Village Credit Institutions Village People Pekutatan terms of aspects Capital, Assets, Earnings, and Liquidity obtained by total final value respectively by 100, it is given a healthy predicate. Traditional Village Pekutatan Village Credit Institutions role in moving the social economy of rural communities is not a financial institution that is solely for the benefit / pure business concept but as a socially minded funding institutions regilius.